Factors impacting the commercial potential of technologies: expert approach - Zemlickienė, Vaida; Mačiulis, Alminas; Tvaronavičienė, Manuela (Technological and Economic Development of Economy, 2017)
In order to ensure the harmonious activity of the institutions engaged in R&D and to reduce the uncertainty of the commercialization of technologies, an advanced tool for verifying decisions on technology development at early stages of commercialization, i.e. an instrument for assessing the commercial potential of technology, is needed. The article is aimed at defining the importance of factors in the commercial potential of technologies with the help of expert research. To achieve the goal, the following tasks have been approached: (1) on the basis of the created system for factors in the commercial potential of technologies, to conduct expert research aimed at collecting information on the importance of factors in technologies; (2) to apply the methods of mathematical statistics in order to determine the compatibility level of expert opinions and the significance of factors. The system of factors in the commercial potential of technologies and the identified significance of factors can be used as recommended guidelines for technology developers, investors and potential owners in the decision-making processes of commercialization, investment or purchase of technology as well as at the next stage of research on the development model for assessing the commercial potential of technologies.